LKPD Development Training (Student Worksheet) Based on Malay Culture for Elementary School Teachers in Bukit Raya Pekanbaru District: Pelatihan Pengembangan LKPD (Lembar Kerja Peserta Didik) Berbasis Budaya Melayu Bagi Guru-Guru SD Se-Kecamatan Bukit Raya Pekanbaru - Sri Rezeki; Dedek Andrian; Putri Wahyuni; Mega Berlin; Zendyah (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
A learning tool in the form of LKPD is essential in learning activities because LKDP measures students' original abilities from learning activities with a certain learning approach. The implementation of this service is motivated by the lack of knowledge and experience of elementary school teachers in developing LKPD and integrating it with culture. This service aims to provide the expertise and ability of teachers to develop tools and integrate them with culture. The service is carried out by giving workshops to Cluster 3 Se District of Bukit Raya teachers. The service results showed that all teachers were enthusiastic about participating in the activities. This is evidenced by several teachers who immediately asked questions during the service process. The teacher asked if all subjects could be integrated with Malay culture. In addition, the teacher asked what steps need to be taken to develop or design LKPD based on Riau Malay culture. Abstrak Perangkat pembelajaran berupa LKPD sangat penting dalam kegiatan pembelajaran karena LKDP mengukur kemampuan asli siswa dari kegiatan pembelajaran dengan pendekatan pembelajaran tertentu. Pelaksanaan pengabdian ini dilatarbelakangi oleh minimnya pengetahuan dan pengalaman guru SD dalam mengembangkan LKPD dan mengintegrasikannya dengan budaya. Layanan ini bertujuan untuk memberikan keahlian dan kemampuan guru untuk mengembangkan perangkat dan mengintegrasikannya dengan budaya. Pengabdian dilakukan dengan memberikan workshop kepada guru-guru Gugus 3 Se Kecamatan Bukit Raya. Hasil pengabdian menunjukkan semua guru antusias mengikuti kegiatan. Hal ini dibuktikan dengan beberapa guru yang langsung bertanya pada saat proses pelayanan. Guru menanyakan apakah semua mata pelajaran bisa diintegrasikan dengan budaya melayu. Selain itu, guru menanyakan langkah-langkah apa yang perlu dilakukan untuk mengembangkan atau merancang LKPD berbasis budaya Melayu Riau.